Giant IgG4-Related Pseudotumor of the Esophagus Resected with Endoscopic Submucosal Dissection: A Case Report and Review of the Literature - Nese EKINCI; Duygu UNAL KOCABEY; Eylul GUN; Fatih ASLAN (Federation of Turkish Pathology Societies, 2021)
IgG4-related disease (IgG4-RD) is a systemic autoimmune disorder that has been defined in various organs. The disease is characterized by typical clinicopathological features including a dense lymphoplasmacytic infiltrate rich in IgG4 positive plasma cells, storiform fibrosis, obliterative phlebitis, and often an elevated serum IgG4 level. Esophageal IgG4-RD is rare, and its presentation as a solid mass is even more rare. Only 15 previous cases of IgG4-related esophageal disease have been described. We herein present a case of giant IgG4-related pseudotumor of the esophagus resected with endoscopic submucosal dissection (ESD) and a review of the literature. The patient was a 67-year-old man who was admitted to our hospital for assessment of progressive dysphagia. Upper gastrointestinal endoscopy revealed a 9 cm mass in the cervical esophagus. In the previous two hospitals, the patient-s mass could not be diagnosed despite repeated biopsies. Because of concerns regarding malignancy, endoscopic submucosal dissection was performed. Histopathological examination showed dense lymphoplasmacytic infiltration with predominant IgG4-positive plasma cells on a sclerotic background. The patient was diagnosed with IgG4-RD. During the follow-up, no residual mass was detected but the patient was diagnosed with lung adenocarcinoma. We present a unique case of giant IgG4-related pseudotumor of the esophagus. Resection with ESD of such a big mass of IgG4-RD in the esophageal region has never been reported before in the literature.